Conventional Interaction of Participants of Contract System Concerning Increase of its Innovative Potential - Anna Mikhaelovna Kuzmina (Управленческое консультирование, 2018)
The role communicative the practician of participants of contract system within increase of its innovative potential in modern conditions is presented in article. The author staticizes conventional nature of communications and interaktion of participants of the contract relations for stimulation of innovations in purchasing activity.